2007
DOI: 10.1109/iembs.2007.4353594
|View full text |Cite
|
Sign up to set email alerts
|

Automatic segmentation of chromosomes in Q-band images

Abstract: Karyotype analysis is a widespread procedure in cytogenetics to assess the possible presence of genetics defects. The procedure is lengthy and repetitive, so that an automatic analysis would greatly help the cytogeneticist routine work. Still, automatic segmentation and full disentangling of chromosomes are open issues. We propose an automatic procedure to obtain the separated chromosomes, which are then ready for a subsequent classification step. The segmentation is carried out by means of a space variant thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…2 (a). Additionally, we tested our algorithm for chromosomes from a high quality dataset from Ruggeri et al, [4] the results of geometrical correction have been shown, Fig. 3 (c).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…2 (a). Additionally, we tested our algorithm for chromosomes from a high quality dataset from Ruggeri et al, [4] the results of geometrical correction have been shown, Fig. 3 (c).…”
Section: Resultsmentioning
confidence: 97%
“…Use of MAT [1], [6]- [7] and infinite thinning [8] has been previously used to obtain a medial axis to correct the shape of the chromosome. Different methods of geometric correction using vessel-tracking algorithm [4], and by segmenting the chromosome into polygons have also been proposed [3]. Most of these algorithms obtain an initial guess and extrapolate it to obtain the medial axis, which is then used for geometric correction.…”
Section: Introductionmentioning
confidence: 99%
“…Metaphase is the stage of cell division at which the chromosomes are most suitable for analysis. [5,9]. A normal human diploid cell contains 22 pairs of chromosomes, autosomes of classes 1-22 and 2 sex chromosomes, either XX or XY.…”
Section: Introductionmentioning
confidence: 99%
“…Metaphase is the stage of cell division at which the chromosomes are most suitable for analysis. [2,3,5]. A normal human diploid cell contains 22 pairs of chromosomes, autosomes of classes 1-22 and 2 sex chromosomes, either XX or XY.…”
Section: Introductionmentioning
confidence: 99%